ANALISIS PENGARUH PEMASARAN BERBASIS PENGALAMAN DAN KUALITAS LAYANAN TERHADAP MINAT KUNJUNG ULANG DENGAN KEPUASAN PENGUNJUNG SEBAGAI VARIABEL MEDIASI (Studi Empiris pada Obyek Wisata Grand Puri Maerokoco Semarang) - Ramdhani, Adinda Sekar; Astuti, Sri Rahayu Tri (Faculty of Economics and Business Diponegoro University, 2019)
This study aims to analyse the impact of experiential marketing and service quality in order to influence revisit intention which visitor satisfaction was used as intervening variable on Grand Puri Maerokoco, one of tourism sites in Semarang. The variables used in this study are experiential marketing and service quality as independent variables, visitor satisfaction as an intervening variable, and revisit intention as a dependent variable.The population in this study is citizens of Semarang City who have visited Grand Puri Maerokoco at least once. The number of samples used was 135 respondents. This study used Structual Equation Modeling (SEM) analysis technique using Amos 23.0 as the analysis instrument.The result shows that experiential marketing and service quality have indirect, positive, and significant effect on revisit intention, using visitor satisfaction as intervening variable. However, experiential marketing and service quality are not significantly influenced revisit intention.